ADNP Upregulation Promotes Bladder Cancer Cell Proliferation via the AKT Pathway - Zhu, Shuai; Xu, Zhenzhou; Zeng, Yong; Long, Ying; Fan, Gang; Ding, Qi; Wen, Yuheng; Cao, Jian; Dai, Tao; Han, Weiqing; Xie, Yu (Frontiers in Oncology, 2020)
Background: Activity-dependent neuroprotective protein (ADNP), which is involved in embryonic development and neurogenesis, has been proven to be upregulated in some human tumors. However, its role in bladder cancer (BC) has never been studied. Objective: we aimed to investigating the mechanisms by which ADNP promotes the progression of BC. Methods: ADNP expressions in BC cell lines and paired BC and adjacent normal tissues were measured by quantitative real-time PCR, Western blot and immunohistochemistry. Colony formation, Cell Counting Kit-8 (CCK-8), trypan blue exclusion assay, flow cytometry and nude micetumorigenesis assay were performed to explore the effects of ADNP on growth of BC in vivo and in vitro. The impacts of ADNP on AKT signaling pathways were measured by Western blot. Results: The expression of ADNP mRNA and protein was significantly upregulated in BC tissues compared with the adjacent normal tissue. Immunohistochemical analysis of 221 BC and 51 adjacent normal tissue paraffin sections indicated that ADNP expression was significantly associated with histological classification and pathological T and N stages. Survival analysis revealed that patients with high ADNP expression have worse prognosis with respect to overall survival and progression-free disease. ADNP knockdown markedly delayed propagation of BC in vitro and the development of BC in vivo; Similarly, ADNP overexpression showed the opposite effect. In addition, ADNP can markedly promote G1-S cell cycle transition in BC cell. On the molecular level, we confirmed that ADNP-mediated acceleration of G1-S transition was associated with activation of the AKT pathways in BC. Conclusion: ADNP is overexpressed in BC and promotes BC growth partly through AKT pathways. Besides, ADNP is crucial in predicting the outcome of BC patients and may be a potential therapeutic target in BC.